A educação especial e a formação de professores proposta pelo programa "Educação inclusiva: direito à diversidade". - Matos, Neide da Silveira Duarte de (2011)
This dissertation results of a bibliographic and documental research about the teachers' education and an analytic study of governmental published material, with emphasis in Special Education/ Inclusive Education modality. This study had as general objectives to study the constitution of the educational service to people with disability and the teachers education request; investigating the teacher's educations in the present times, under the light of Critical-Historic Pedagogy and Cultural-Historic psychology; Comprehend the politic of teachers' education proposed by Teachers' Inclusive Education Program: right to diversity , from Education Ministry (MEC- Brazil), initiated in 2003. This research justified in face of need for materials about this, as well as the necessity of the theoretical orientation for the development of the educational practice that is developed in the municipal district. It was identified that the context of reform of 1990 brought implications for the educational process and, therefore, for the teachers formation. In that time, the hegemonic speech was that the public school needed to give answers to the daily problems. However, in general, deviating them of the materiality that the live inflict to the men from those years. And, as a strategy for the necessarily changes, it was elected the professor professionalization, with improvement courses and continued formation - after graduation. With this politic, the propose of qualification of the professors would be solving educational problems and indirectly, economics and politics problems. In this way, the analyzed Program wouldn't be out of this perspective. As results of the research, highlights the Inclusive Education Program: right to diversity , as others initiatives of formations, represent the product and also produce politics orientations that were and are present. In this way, express the context of influence and production of educational legislation after reform. It follows that in the capitalist society the formation of the worker is always submitted to the conditionality that the way and the relations of products are presented. It was noticed that the limits of this organized form of society directed the process of teachers' education. By this way, it is understand that the objectives and proposes of formation cannot be reached in your plenitude. However, it's necessary that the possibility some true. It defends that the teachers' formation research the theoretical knowledge and this can be rebound, in fact, at teachers work.